Afraid [videorecording (DVD)] - Weitz, Chris, 1969-; Cho, John, 1972-; Waterston, Katherine; Liu, Havana Rose, 1997-; Drosche, River; Youcef, Ben; Joyce, Mason Shea; Hill, Greg (Actor); Bright, Ashton Essex; Eliot, Jason Silva; Aguirresarobe, Javier, 1948-; Weston, Alex (Composer) (Sony Pictures Home Entertainment, 2024)
Curtis and his family are selected to test a revolutionary new home device: a digital family assistant called AIA. Taking smart home to the next level, once the unit and all its sensors and cameras are installed in their home, AIA seems able to do it all. She learns the family's behaviors and begins to anticipate their needs. And she can make sure nothing - and no one - gets in her family's way.